Implementation of drone HTP phenotyping in multiple sites globally - CGIAR Research Program on Rice (2018)
New HTP platforms and facilities were deployed in the reference panel evaluation in Raipur, Titabar (india) and Palmira (Colombia). Drones used for phenotyping drone based system for Hoja blanca disease classification and developed a prototype for a low-cost and high precision environment.